Systemic mastocytosis: a rare case of increased liver stiffness - Adolf, Stefanie; Millonig, Gunda; Seitz, Helmut K.; Reiter, Andreas; Schirmacher, Peter; Longerich, Thomas; Mueller, Sebastian (Case reports in hepatology, 2012)
Assessment of liver stiffness (LS) by transient elastography (Fibroscan) has significantly improved the noninvasive diagnosis of liver fibrosis. We here report on a 55-year-old patient with drastically increased LS due to previously unknown systemic mastocytosis. The patient initially presented with increased weight loss, nocturnal pruritus, increased transaminases, bilirubinemia, and thrombocytopenia. Abdominal ultrasound showed ascites, hepatomegaly, and splenomegaly. In addition, LS was 75 kPa (IQR 0 kPa) clearly exceeding the cut-off value for F4 cirrhosis of 12.5 kPa. However, histological analysis of the liver specimen indicated liver involvement by systemic mastocytosis and excluded liver cirrhosis. An additional CT scan detected disseminated bone lesions. After three months of treatment with Midostaurin, LS slightly decreased down to 31.9 kPa (IQR 8.3 kPa). This case illustrates that diffused sinusoidal neoplastic infiltrates are a pitfall in the non-invasive diagnosis of liver cirrhosis. In conclusion, refined clinical algorithms for increased LS should also include mastocytosis in addition to inflammation, congestion, and biliary obstruction.